Case Report: Murine typhus complicated by symmetrical peripheral gangrene: first report and diagnostic insights from metagenomic next-generation sequencing - Zhu, Hengling; Hu, Linhui; Feng, Zaiming; Zhang, Zichen; Zhu, Hengbao; Li, Huihua (Frontiers in Immunology, 2026)
BackgroundMurine typhus, a flea-borne infection caused by Rickettsia typhi, often presents with nonspecific symptoms that delay diagnosis. While usually self-limiting, it can rarely progress to multiple organ dysfunction syndrome (MODS). We report the first case of murine typhus complicated by symmetrical peripheral gangrene (SPG), in which metagenomic next-generation sequencing (mNGS) enabled rapid diagnosis and guided timely doxycycline therapy.Case presentationA 69-year-old female from South China was hospitalized with persistent abdominal pain and low-grade fever. She was a farmer and had suspected animal exposure. Laboratory investigations revealed hypoxia, abnormal coagulation profile, hepatorenal impairment, and thrombocytopenia. Despite empirical antibiotic therapy, her condition deteriorated progressively, manifested as hemodynamic instability, respiratory failure, and the emergence of purpuric-petechial cutaneous eruptions. Immediate interventions were initiated, including administration of vasoactive agents and mechanical ventilation. Based on mNGS, R. typhi was confirmed, she received targeted antibiotic treatment with intravenous doxycycline (100 mg twice daily). On the hospital day 16, gangrene of all four extremities became evident. The patient underwent amputation of all four extremities and survived, with systemic symptoms gradually resolving during 6-months follow-up.ConclusionThis first reported case of murine typhus complicated by symmetrical peripheral gangrene (SPG) establishes its potential to cause life-threatening multiorgan failure. Metagenomic next-generation sequencing (mNGS) resolved the diagnostic challenge by rapidly identifying Rickettsia typhi, guiding life-saving doxycycline therapy and underscoring its value in severe zoonotic infections.